The impact of random help on the dynamics of indirect reciprocity - Charlotte Klempt (Institut für Angewandte Wirtschaftsforschung (IAW), 2012)
Cooperation via indirect reciprocity uses a partner's reputation to enable subjects to direct help to those who cooperated themselves. As a partner's reputation provides information whether the partner helped a third party in the past or not, subjects can help those partners with a good reputation. Whereas help in former studies implied a definite monetary transfer to a third party, the present study explores the implications for cooperation via indirect reciprocity if a helping decision does not necessarily involve a monetary transfer. The study employs a 'repeated helping game' where a chance move determines whether help actually leads to a reward for the recipient or not. Hence, a good reputation may not coincide with a positive income for the third party. The experimental results show that, firstly, if a chance move determines the outcome of helping decisions, the information about the past decision of partners has a smaller effect on cooperation rates as compared to a situation where helping decisions definitely lead to rewards. This suggests that risk substantially influences the dynamics of indirect reciprocity. Secondly, subjects only reciprocate the recipient's good reputation and disregard whether a good reputation also involves a beneficial outcome for the third party. Here, findings oppose those found in studies on direct reciprocity where both the player's good intentions or good will and the actual monetary amount transferred affect reciprocal back-giving.
Keywords: C91; D8; 330; Indirect reciprocity; Reputation; Cooperation